Extending the time window for intravenous thrombolysis in acute ischemic stroke using magnetic resonance imaging-based patient selection - Ringleb, Peter A.; Bendszus, Martin; Fatar, Marc; Hacke, Werner (International journal of stroke, 2019)
Background: Intravenous thrombolysis with alteplase within a time window up to 4.5 h is the only approved pharmacological treatment for acute ischemic stroke. We studied whether acute ischemic stroke patients with penumbral tissue identified on magnetic resonance imaging 4.5-9 h after symptom onset benefit from intravenous thrombolysis compared to placebo.
Gesehen am 21.10.2019